ACCURACY OF RAPID TEST OF STORED ACUTE PHASE SERUM FOR DIAGNOSE JAPANESE ENCEPHALITIS - Subanada, Ida Bagus; Kari, I Komang (Medicina, 2013)
Japanese encephalitis (JE) is common viral encephalitis with high sequele and mortality. With some limitations, there are several diagnostic tool to diagnose of JE. The objecive of this study was to know the accuracy of rapid test of stored acute phase serum for diagnose of JE. We conducted diagnostic test of stored acute phase serum of encephalitis patients with MAC ELISA of cerebrospinal fluid as a gold standard. Sensitivity, specificity, positive predictive value (PPV), negative predictive value NPV), positive likelihood ratio (PLR), negative likelihood ratio (NLR), and post-test probability were calculated. This study found the prevalence of JE was 42.1%, sensitivity 15.7 % (95% CI 9.2 to 22.2%), specificity 95.7% (95% CI 92.1 to 99.3%), PPV 72.7% (95% CI 64.8 to 80.6%), NPV 60.9% (95% CI 52.2 to 69.6%), PLR 3.7, NLR 0.9, and post-test probability was 0.73. We concluded that rapid test of acute phase stored serum was insensitive but specific to diagnose of JE.